Current issues in research communications: adding value and sharing research - 3rd report to JISC, December 2010 - Hubbard, Bill; Hodgson, Amanda; Fuchs, Willow (Centre for Research Communications, 2010)
This report looks at the scope of current OA practice and the opportunities it offers for innovation in scholarly communication methods. Among the questions it discusses are: • Why are some researchers still reluctant to embrace open access? • What kinds of "added value" in scholarly communication can be attached to open access? • What is the significance for scholarly communications practice of the growth of social networking/reference management systems such as Mendeley?